Anthropometric profile and body composition of the Mexican Olympic beach volleyball team - Barajas-Pineda, L.; Salazar-C., C. M.; Flores-Moreno, P. J.; Gomez-Figueroa, J. A.; Andrade-Sanchez, A. I.; Del Rio Valdivia, J. E.; Gomez, E. G. (International Journal of Morphology, 2023)
The present research corresponds to a cross-sectional descriptive study in the anthropometric field, which allows coaches to develop standards to identify talent and optimize training in the discipline of beach volleyball. Its objective was to define the anthropometric profile and body composition of the Mexican Olympic beach volleyball teams in both sexes. The participants were couples one and two of Mexico in both sexes (defined by FIVB ranking), 4 women and 4 men with average age of 30.25±6.85 and 27.25±7.36 years. The technique used was Heath-Carter ´s somatotype method and the anthropometric profile restricted ISAK protocol. Among the findings resulting from the research, unification can be observed in the male morphological characteristics (triceps skinfold, front thigh skinfold, calf skinfold, circumference of relaxed and contracted arm, waist, hip, femur diameter and BMI), as for the somatotype, both sexes of Mexican couples are positioned in mesomorphs-balanced. In relation to other studies consulted, balance in somatotype and muscular development is observed with high performance teams. Weight and height, as well as age, are important variables for the selection of talent and future optimal performance in world and professional volleyball.